Teachers’ perspectives on the absence of gender-diverse voices in South African literature - Nontsikelelo Gabrielis Ndabeni (Eureka: Journal of Educational Research, 2025)
In South African classrooms, literature plays a crucial role in shaping students' identities, yet the literary canon often reflects Eurocentric perspectives that marginalize gender-diverse voices. This paper examined the implications of such exclusions through teachers’ perspectives. Guided by Rosenblatt’s Reader-Response Theory, which viewed meaning as co-constructed by readers’ lived experiences, and Freire's Critical Pedagogy, which framed education as a vehicle for social reform, the study also drew on Sedgwick’s Queer Theory, which interrogated heteronormativity and binary gender constructs while advocating for the disruption of rigid categories to validate diverse identities. Using a qualitative case study design, six purposely selected English teachers from three high schools in the OR Tambo District, Eastern Cape Province, were interviewed. Outcomes revealed that when students do not see their gender identities reflected in texts, they often disengage, affecting their academic performance and sense of belonging. Teachers observed that this exclusion particularly impacted students with nonconforming gender identities, who experienced feelings of invisibility and diminished self-worth. The author recommends a shift to curricula that incorporate both dominant and marginalised gender perspectives, enabling more inclusive and gender-sensitive classrooms. It is believed that inclusive literary practices can affirm diverse subjectivities and foster equitable learning environments that reflect contemporary South African society.